Why Do We Procrastinate? Present Bias and Optimism - Zachary Breig; Matthew Gibson; Jeffrey G. Shrader (Institute of Labor Economics (IZA), 2020)
Research has shown that procrastination has signicant adverse effects on individuals, including lower savings and poorer health. Procrastination is typically modeled as resulting from present bias. In this paper we study an alternative: excessively optimistic beliefs about future demands on an individual's time. The models can be distinguished by how individuals respond to information on their past choices. Experimental results refute the hypothesis that present bias is the sole source of dynamic inconsistency, but they are consistent with optimism. These findings offer an explanation for low takeup of commitment and suggest that personalized information on past choices can mitigate procrastination.
Keywords: D90; D84; D15; J22; 330; discounting; beliefs; dynamic inconsistency; real effort